Folk dances as a happening of coming together in the streets of Athens - Blagojević Gordana (Glasnik Etnografskog Instituta SANU)
The focus of this work, based on my long-term field research in Athens, is the use of open urban spaces (parks, parking lots, and streets) as a gathering place for citizens to practice traditional folk dances.1 The research focuses on dance events organized by informal groups of citizens, not by institutions. Results show that there is a significant presence of folk dances in the streets and parks of Athens. The paper gives special attention to the periodic dance gatherings on the occasion of the Klidonas holiday (June 23/24), International Bagpipe Day (March 10) and Tsampounoglenti in honour of Saint Demetrius (October 26). The paper especially analyzes various aspects of these dance activities, their role in the lives of the participants and at the level of the wider social community. The participants themselves emphasize the importance of folk dances in overcoming alienation, establishing interpersonal connections, and strengthening neighborly relations.